2003
DOI: 10.1111/j.1365-2621.2003.tb14127.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation in the Lipid Quality of Wild and Farmed Seabass (Dicentrarchus labrax) and Gilthead Sea Bream (Sparus aurata)

Abstract: The elements of differentiation that characterize the quality of the lipid fraction of wild and farmed sea bass (Dicentrarchus labrax) and gilthead sea bream (Sparus aurata) were investigated. Reared fish of either species had a total lipid content significantly higher than the wild counterparts. Liquid chromatography of unsaponifiable lipids showed, on a lipid gram basis, higher cholesterol levels in wild fish and comparable amounts of squalene, alltrans retinol, and a-tocopherol. Gas chromatography of total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
81
3
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 16 publications
27
81
3
1
Order By: Relevance
“…In the present study, protein rate of wild sea bass was 6.27% and more than cultured sea bass. The results showed similarity with the results of the studies conducted by Erdem (2006) in brook trout and by Orban et al (2003) in gilt-head breams and sea bass but showed differences with the results of the study of Yıldız et al (2007) in sea bass. This difference might arise from the fish size, environment and the feed content.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…In the present study, protein rate of wild sea bass was 6.27% and more than cultured sea bass. The results showed similarity with the results of the studies conducted by Erdem (2006) in brook trout and by Orban et al (2003) in gilt-head breams and sea bass but showed differences with the results of the study of Yıldız et al (2007) in sea bass. This difference might arise from the fish size, environment and the feed content.…”
Section: Resultssupporting
confidence: 77%
“…al. (2007), Alasalvar (2002) and Orban et al (2003) in sea bass, by Erdem (2006) in brook trout and by Nowosad et al (2015) in European eel. Protein quality is determined by the quantity of essential amino acids in protein.…”
Section: Resultsmentioning
confidence: 99%
“…Increased flesh lipid in farmed compared to wild European sea bass has been reported in the literature (21,28,29), although a recent study reported no difference in flesh lipid between farmed and wild fish (22). Similarly elevated flesh lipid levels in farmed versus wild fish have also been reported for gilthead sea bream (Sparus aurata) (29,30), red porgy (Pagrus pagrus) (31), rainbow trout (Oncoryhchus mykiss) (20), and Atlantic salmon (Salmo salar) (32). These data suggest that the intensive culture of sea bass using diets with a lipid content of ∼20% results in increased lipid deposition in farmed bass compared to wild fish.…”
Section: Discussionmentioning
confidence: 99%
“…The pyrolysis gases then passed through a carbosorb/magnesium perchlorate trap to remove traces of CO 2 and water, respectively, and thereafter through a packed 50 cm × 6 mm i.d. GC column filled with molecular sieves of 5 Å held at 30°C to separate H2, N2, and CO. A portion of the effluent was allowed to flow into the ion source of the IRMSr (ThermoFinnigan, TracerMAT), and the 18 29.32‰ vs VSMOW) was used. The use of a matrix standard allowed correction for this drift in addition to the normal drift correction, specific to the IRMSr.…”
Section: Methodsmentioning
confidence: 99%
“…The increase in the pH value occurs owing to the effects of ammonia and other similar volatile base compounds as a result of the decomposition. The pH value in culture sea bass found by Periago et al (2005) and Orban et al (2003) were 6.44 and 6.27 respectively. In our study, pH values were lower than 7.00 for all samples and they were in acceptable quality.…”
Section: Ph Analysis Resultsmentioning
confidence: 93%